2017
DOI: 10.1111/jpc.13779
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between cystic biliary atresia and choledochal cyst: A retrospective analysis

Abstract: There is still certain difficulty in the early identification of CBA and CC clinically. Liver fibrosis could occur as early as infantile period in both CBA and CC. In infants with BCMs, APRI can be used as a non-invasive method to detect liver fibrosis in early stages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
2
2
0
1
Order By: Relevance
“…During the same period, the lesions affecting liver function in children with CCs were milder than those in children with CBA, which was likely the cause of the less critical cholestasis. The ALT, AST, TBIL, and DBIL levels in the CBA group were all significantly higher than those in the CC group in this study, which was consistent with the results reported in several existing studies ( 17 ). This indicated that these indexes could be used as sensitive indicators to distinguish CBA from CCs.…”
Section: Discussionsupporting
confidence: 93%
“…During the same period, the lesions affecting liver function in children with CCs were milder than those in children with CBA, which was likely the cause of the less critical cholestasis. The ALT, AST, TBIL, and DBIL levels in the CBA group were all significantly higher than those in the CC group in this study, which was consistent with the results reported in several existing studies ( 17 ). This indicated that these indexes could be used as sensitive indicators to distinguish CBA from CCs.…”
Section: Discussionsupporting
confidence: 93%
“…Diagnostic confusion of cystic biliary atresia with congenital choledochal cyst might have been the cause of the delayed diagnosis in some cases in this study, as previously reported (12,13). At the time of diagnosis, obstructed congenital choledochal cyst needs to be differentiated from cystic biliary atresia (14–16).…”
Section: Discussionsupporting
confidence: 68%
“…In a previous study, the most frequently described difference between cBA and CC was the cyst size. Several studies mentioned that cysts were significantly smaller on postnatal US in cBA than in CC, with cutoff values ranging from 1.5 to 3.5 cm [5,[24][25][26]. Even though the cyst size in cBA can be variable, and cysts can extend below the hepatic hilum, the cysts in infants with cBA were also significantly smaller than those in infants with CC in our study.…”
Section: Discussionmentioning
confidence: 45%
“…cBA can be misdiagnosed as CC, especially when the cyst is large and not limited to the periportal tract. However, it is important to differentiate these two disease entities early in infancy because they have different clinical outcomes without an early intervention [24]. Our study showed that an increased triangular cord thickness (cutoff value of 4 mm on US, the same cutoff as in the original research on BA [10]), smaller cyst size, GB mucosal irregularity, and non-visibility of the distal bile duct on US or MRI were the key diagnostic features for differentiating cBA from CC type Ia/b, with excellent diagnostic performance, even though T.bil and γGT levels were not significantly different between the two groups.…”
Section: Discussionmentioning
confidence: 99%